Komunikasi Non Verbal Anak Autis pada Masa Adaptasi Pra Sekolah - Mutia Rahmi Pratiwi; Lisa Mardiana; Amida Yusriana (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2019)
Every children has distinguished life, likewise the life of the children with autism.Children with autism frequently considered as odd because they seems like havingtrouble in paying attention and are uninterested to social life. Indonesia does not have theprecise number of the children with autism and it has been increased every year.Education is one of the medium for children with autism to learn the standard way ofbehaviour that socially acceptable. The kindergarten is the first non formal school forchildren with autism. However, the autism’s disability often fails the communicationprocess at school. The rejection will be unavoidable for the first initial meetings. Thisphenomenon becomes the main attraction for the researcher to analyze the behaviour ofchildren with autism in the kindergarten. This is a qualitative research and using thephenomenology method. The objects of the research is M, W and D. They are the childrenwith autism at the informal school of Widya Bhakti Semarang. The aim of this research isto describe the non verbal communication of children with autism as the efforts ofadaptation in the kindergarten.